Coping mechanisms in mental health of oncopediatric ICU workers: an integrative review (Research, Society and Development, 2020)
Psychosocial risks among health workers have been the subject of national and international research. In this sense, we turn to oncopediatric intensive care workers, who constantly deal with extreme situations making them vulnerable to emotional exhaustion and consequently looking for possible coping mechanisms. Objective: To identify productions that aim the value the quality of life of oncopediatric intensive care workers, through successful interventions. Method: Integrative review conducted in August 2019 through the search for original and available articles, published in the last 5 years with the theme of the valorization of the quality of life of the health workers with high emotional demand, in the oncopediatric intensive care environment. Online research conducted on the VHL portal, databases: LILACS, PUBMED, MEDLINE and CAPES. Results: The sample resulted in 09 publications of which only one evaluates the occupational risk suffered in pediatric intensive care, while the others report the presence of feelings of negative emotional load and coping mechanisms adopted by health professionals. Numerous strategies are highlighted involving spirituality, resilience, individual and collective support techniques. Conclusion: Continuous assistance to those who are suffering gives rise to feelings that influence the lives of professionals in general, making them vulnerable to psychosocial risks. Improving the worker's ability to deal with situations of suffering with high emotional impact with equanimity and compassion is an initiative that not only promotes mental health but also favors effective care.